HEADING PERMAINAN SEPAK BOLA MELALUI PEMBELAJARAN PERSONAL PADA SISWA SMPN 4 SUNGAI RAYA - Putra, Randika Jauhari; Purnomo, Edi; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakHeading game when learning soccer in SMP Negeri 4 Sungai Raya school has never been explored through real data means that there needs to be a research method that can help to get the data, the purpose of this study is to improve the soccer game heading with a personal system The research method used is classroom action research or clas research room where research is carried out for improvement in a particular class, classroom action research is carried out when learning takes place in two cycles in which there are planning, implementation, evaluation and reflection in followed by 25 students of SMP NegeriI 4 , Sungai RayaThe results of the research carried out by researchers were obtained at the time of the cycle one - the average final score reached 74.3 or only 17 students and those who had not yet graduated were still 8 students in the second cycle the average score was 76.6 with completeness of 22 students there are still 3 studentsÂ who have not been told that complete means that when the learning process is completed above 70% then it does not need to proceed to the third cycle.The conclusion that can be conveyed is that there is an increase in ball heading with a personal system method for students in SMPNegeri 4 Sungai RayaKeywords: Heading, Soccer, Personalized System